Pareto-optimal predictor composite formation: A complementary approach to alleviating the selection quality/adverse impact dilemma - SACKETT, Paul R. (Institutional Knowledge at Singapore Management University, 2008)
In our rejoinder to the comments of Kehoe (this issue) and Potosky, Bobko and Roth (this issue) we emphasize that our proposal on Pareto-optimal predictor composite formation is a complementary and not a competitive alternative for reducing the tension between selection quality and adverse impact. Our work addresses the decisions to be made once one has decided to use a predictor composite. We also further clarify the basic features of Pareto-optimal tradeoffs and Pareto-optimal composites within the context of personnel selection. In particular, we indicate that Pareto-optimal tradeoffs between validity and adverse impact emerge because these goals are different and not because of any dualism between them.